The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/foods10122927
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Microbial Decontamination of Cereals by Non-Thermal Plasma

Abstract: Cereals, an important food for humans and animals, may carry microbial contamination undesirable to the consumer or to the next generation of plants. Currently, non-thermal plasma (NTP) is often considered a new and safe microbicidal agent without or with very low adverse side effects. NTP is a partially or fully ionized gas at room temperature, typically generated by various electric discharges and rich in reactive particles. This review summarizes the effects of NTP on various types of cereals and products. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 73 publications
0
14
0
1
Order By: Relevance
“…NTP has already shown promising results in the fields of medicine [ 14 , 15 , 16 , 17 , 18 ], in the textile industry [ 19 , 20 , 21 ], in forestry [ 22 , 23 ], in the food industry [ 24 , 25 , 26 ], and in the food preservation industry [ 27 , 28 , 29 , 30 ]. With so much knowledge about NTP and its established diverse applications, the focus has also shifted towards the agriculture sector (known as ‘plasma agriculture’ [ 31 ]) in recent years, as there are calls for new and clean technologies to replace chemical pesticides that are growing around the world. Several research articles have demonstrated that NTP can potentially improve seed germination and crop yield [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…NTP has already shown promising results in the fields of medicine [ 14 , 15 , 16 , 17 , 18 ], in the textile industry [ 19 , 20 , 21 ], in forestry [ 22 , 23 ], in the food industry [ 24 , 25 , 26 ], and in the food preservation industry [ 27 , 28 , 29 , 30 ]. With so much knowledge about NTP and its established diverse applications, the focus has also shifted towards the agriculture sector (known as ‘plasma agriculture’ [ 31 ]) in recent years, as there are calls for new and clean technologies to replace chemical pesticides that are growing around the world. Several research articles have demonstrated that NTP can potentially improve seed germination and crop yield [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been devoted to the effects of direct plasma application on germination and other properties of seeds, including wheat; the germination of Penicillium spores may be also affected [ 8 ]. References [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] are several recent works in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a great interest in finding new, alternative approaches for grain treatment. Cold plasma (CP) treatment techniques seem to offer us potential as a green technology for surface disinfection to prevent fungal growth on seeds and grains [ 10 , 11 ] while avoiding chemical inputs. Besides its antimicrobial activity, CP treatment or treatment with plasma-activated water (PAW) can also stimulate seed germination, enhance growth, and improve the stress tolerance of plants [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%